Unraveling the geometry of the New England oroclines (eastern Australia): Constraints from magnetic fabrics - Mochales, T.; Rosenbaum, G.; Speranza, F.; Pisarevskiy, Sergei (American Geophysical Union, 2014)
The southern New England Orogen (NEO) in eastern Australia is characterized by tight curvatures(oroclines), but the exact geometry of the oroclines and their kinematic evolution are controversial. Here we present new data on the anisotropy ofmagnetic susceptibility (AMS), which provide a petrofabric proxy for the finite strain associated with the oroclines.We focus on a series of preoroclinal Devonian-Carboniferous fore-arc basin rocks, which are aligned parallel to the oroclinal structure, and by examining structural domains, we test whether or not the magnetic fabric is consistent with the strain axes. AMS data show a first-order consistency with the shape of the oroclines, characterized, in most of structural domains, by subparallelism between magnetic lineations, “structural axis” and bedding. With the exception of the Gresford and west Hastings domains, our results are relatively consistent with the existence of the Manning and Nambucca (Hastings) Oroclines. Reconstruction of magnetic lineations to a prerotation (i.e., pre–late Carboniferous) stage, considering available paleomagnetic results, yields a consistent and rather rectilinear NE-SW predeformation fore-arc basin. This supports the validity of AMS as a strain proxy in complex orogens, such as the NEO. In the Hastings Block, magnetic lineations are suborthogonal to bedding, possibly indicating a different deformational historywith respect to the rest of the NEO.